MEGG RAYARA GOMES DE OLIVEIRA: FIRST BLACK TRANSGENDER PhD OF BRAZIL - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Megg Rayara Gomes de Oliveira was born on October 8, 1975, in Cianorte, in the countryside of Paraná. As she says, she was a “fag” with a “silly” sexuality, so at school, she was introduced to these rules in a very violent way. Artistic production appeared in her life as a possibility of transgression and communication with manifestations of her inner self. She entered the Licentiate Degree program in Drawing and Plastics and, after failing four times in the master’s degree, she was aware that the academy had its standard features. In 2017, she became the first black transgender to obtain the title of doctor in Brazil. In 2019, she was appointed as a Professor at the Federal University of Paraná (UFPR) and is currently the coordinator of the Center for Afro-Brazilian Studies (NEAB) at UFPR.